Autoantibodies targeting TLR and SMAD pathways define new subgroups in systemic lupus erythematosus. (July 2018) - Lewis, Myles J.; McAndrew, Michael B.; Wheeler, Colin; Workman, Nicholas; Agashe, Pooja; Koopmann, Jens; Uddin, Ezam; Morris, David L.; Zou, Lu; Stark, Richard; Anson, John; Cope, Andrew P.; et al.
Abstract: Objectives: The molecular targets of the vast majority of autoantibodies in systemic lupus erythematosus (SLE) are unknown. We set out to identify novel autoantibodies in SLE to improve diagnosis and identify subgroups of SLE individuals. Methods: A baculovirus-insect cell expression system was used to create an advanced protein microarray with 1543 full-length human proteins expressed with a biotin carboxyl carrier protein (BCCP) folding tag, to enrich for correctly folded proteins. Sera from a discovery cohort of UK and US SLE individuals (n = 186) and age/ethnicity matched controls (n = 188) were assayed using the microarray to identify novel autoantibodies. Autoantibodies were validated in a second validation cohort (91 SLE, 92 controls) and a confounding rheumatic disease cohort (n = 92). Results: We confirmed 68 novel proteins as autoantigens in SLE and 11 previous autoantigens in both cohorts (FDR<0.05). Using hierarchical clustering and principal component analysis, we observed four subgroups of SLE individuals associated with four corresponding clusters of functionally linked autoantigens. Two clusters of novel autoantigens revealed distinctive networks of interacting proteins: SMAD2, SMAD5 and proteins linked to TGF-β signalling; and MyD88 and proteins involved in TLR signalling, apoptosis, NF-κB regulation and lymphocyte development. The autoantibody clusters were associated with different patterns of organ involvement (arthritis, pulmonary, renal and neurological). A panel of 26 autoantibodies, which accounted for four SLE clusters, showed improved diagnostic accuracy compared to conventional antinuclear antibody and anti-dsDNA antibody assays. Conclusions: These data suggest that the novel SLE autoantibody clusters may be of prognostic utility for predicting organ involvement in SLE patients and for stratifying SLE patients for specific therapies. Highlights: Protein microarray reveals molecular identity of 68 novel SLE autoantigens. SLE autoantibodies cluster into four biologically functional groups. SLE autoantigen clusters link to TGF-β/Wnt signalling and TLR signalling/apoptosis regulation. Novel autoantibodies show selectivity for different SLE manifestations (arthritis, renal, thrombocytopenia). 26-autoantibody panel improves diagnostic accuracy compared to conventional serology.